Improved Spread Spectrum: A New Modulation Technique for Robust Watermarking - Malvar, Henrique S.; Florencio, Dinei (IEEE Transactions on Signal Processing, 2003)
This paper introduces a new watermarking modulation technique, which we call improved spread spectrum (ISS). When compared with traditional spread spectrum (SS), the signal does not act as a noise source, leading to significant gains. In some examples, performance improvements over SS are 20 dB in signal-to-noise ratio (SNR) or ten or more orders of magnitude in the error probability. The proposed method achieves roughly the same noise robustness gain as quantization index modulation (QIM) but without the amplitude scale sensitivity of QIM. Our proposed ISS is as robust in practice as traditional SS.